Bussiness Model Canvas: Coconut Flesh Remover / Siti Nur Auni Husna Shikh Mohd Noor - Shikh Mohd Noor, Siti Nur Auni Husna (2020)
The purpose of this report is to give details and explain my product in Business Model Canvas (BMC) form. Before I put my ideas and concept of my product in BMC, I have identify the problems faced by Kak Nah Serondeng Enterprise. After that, I brainstorm the idea by doing a survey to 30 respondents which are mostly the students of UiTM Kota Bharu. From the results of the survey, I be able to quickly draw a picture of what the idea of my product entails. Main problem faced by this company is the process to remove coconut flesh is time consuming and repetitive use of the tool can cause hand pain. This company still using traditional tool to remove coconut flesh. Encik Hafiz said that most is the time, the process of removing the coconut flesh will cause hand pain. This is because the work force is focused only to the hand. Hence, this study was conducted to develop an innovation that will help to reduce hand pain. In addition, this paper will highlight all of the nine building blocks in the business model canvas which are key partners, key activities, key resources, value propositions, channels, customer relationships, customer segments, cost structure and revenue streams